The Effect of Complementary and Alternative Medicine for Treatment of Gliomas: A Comprehensive Systematic Review - Putra, Yosie Yulanda; Lestari, Deby Tri; Auliya, Ahsan; Ananda, Astrid; Syarfina, Afdila; Azhari, Ririn; Merisa L, Bella (International Medical Journal Corp. Ltd, 2024)
Background: Since the majority of GBM patients are aware that there is no known cure, it makes sense that they would want to know about complementary, alternative, and CIM therapies. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Conclusion: complementary and alternative medicine methods to comfor patients with gliomas with the medication side effects that taking control of the disease. The findings of this systematic review helped to educate the providers and patients to stimulate more research according to complementary and alternative medicine for treatment of gliomas.